A Retrospective Analysis of Crayfish-Related Rhabdomyolysis (Haff Disease). (1st July 2019) - Huang, Changbao; Peng, Liangfei; Gong, Nengkai; Xue, Cheng; Wang, Weihua; Jiang, Jinghan
Abstract : Objective . To investigate the epidemiologic and etiologic factors, clinical features, therapeutic regimen, and prognosis of crayfish-related rhabdomyolysis (Haff disease). Methods . Retrospectively analyzed the clinical data of 29 patients with crayfish-related rhabdomyolysis (Haff disease) from July to August 2016, summarized the clinical characteristics, and evaluated the prognosis. Results . Clinical data of a total of 29 cases of Haff disease were retrospectively analyzed. The disease onset occurred after consumption of cooked crayfish with the incubation period ranging from 1 h to 48 h. There were no gender differences and significantly elevated CK in the duration with peak value of 41575.0U/L; the median value was 2445.0U/L (range: from 1187.0 U/L to 4722.0 U/L) and there was coincident elevated CK-MB. There was also no hepatorenal damage and transient urinalysis was abnormal. The most common presenting symptoms were myalgia (100%), weakness and numbness (51.7%), chest tightness and chest pain (41.4%), back pain (41.4%), and extremities pain (37.9%). All the patients recovered and no patients died. Conclusions . Crayfish-related rhabdomyolysis (Haff disease) is a kind of a case or cluster of patients present with severe myalgia or weakness of unknown etiology and mechanism disease; however, the clinical signs and symptoms are relatively mild with favorable outcome.